Peculiarities in the development of a finite element model on the example of a “long bone – rod device” system - Laksha, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
A method for creating finite element models of long bones with use of the Mimics software package is described. In order to construct realistic models, computed tomograms of limb segments were used. The bones were divided into three types on the basis of Hounsfield numbers: compact, spongy and medullary canal. Performance of the “tibia – rod device for external fixation” model is shown in Ansys software environment. Results of investigations for verifying the accuracy of the “tibia – rod device for external fixation” simulation finite element model versus the method of actual bench scale tests are presented. A satisfactory compliance of the calculated and experimental data was found.